PENGARUH PENGGUNAAN PUPUK KANDANG AYAM PEDAGING TERHADAP PERTUMBUHAN BIBIT Indigofera zollingeriana: The Effect of Broiler Chicken Manure Application on the Growth of Indigofera zollingeriana Seedlings - Sari, Nurjanah Puspita; Herawati, Ervi; Rohayati, Tati (Fakultas Pertanian Universitas Garut, 2025)
Abstract Indigofera zollingeriana is a leguminous plant that can be used as livestock feed due to its high protein content. This study aimed to determine the effect of different doses of broiler chicken manure on the growth of Indigofera zollingeriana seedlings. The research was conducted in Margawati Subdistrict, Garut Kota District, Garut Regency, from June to August 2024. The study utilized a Randomized Block Design (RBD) with five treatments and five repetitions. The treatments consisted of broiler chicken manure doses: P0 = 0 g, P1 = 200 g, P2 = 400 g, P3 = 600 g, and P4 = 800 g. The results indicated that the application of broiler chicken manure significantly influenced the growth of Indigofera zollingeriana seedlings. The dose of 400 g (P2) yielded the best results for plant height, number of leaves, number of branches, and stem diameter of Indigofera zollingeriana seedlings. Keywords: Indigofera zollingeriana, broiler chicken manure, dosage.